The genus Labiobaetis (Ephemeroptera: Baetidae) in China, with description of a new species - Shi, Weifang; Tong, Xiaoli (Zootaxa, 2014)
Five species of the genus Labiobaetis (Baetidae) are recognized from China based on mature nymphs, including a new species, Labiobaetis ancoralis n. sp. and a new combination, Labiobaetis mustus (Kang & Yang) n. comb. The new species differs from L. multus (Müller-Liebenau) and L. pulchellus (Müller-Liebenau & Hubbard) by the spatulate submarginal setae on labrum and the apical segment of maxillary palpus with a pronounced excavation near apex. Imago stage of L. mustus (Kang & Yang) n. comb. is described for the first time based on male and female imagoes reared from nymphs, which can be distinguished from other known imagoes of Labiobaetis by the color pattern of abdominal terga and hind wing having a tiny vestigial costal process. All Oriental species previously transferred to Pseudocloeon are reassigned to Labiobaetis in the present paper. An identification key is provided to the known mature nymphs of Oriental Labiobaetis species.